Corneal Densitometry After Small Incision Lenticule Extraction (SMILE) and Femtosecond Laser-Assisted LASIK (FS-LASIK): 5-Year Prospective Comparative Study - Wei, Ruoyan; Li, Meiyan; Yang, Weiming; Shen, Yang; Zhao, Yu; Fu, Dan; Shang, Jianmin; Zhang, Jing; Choi, Joanne; Zhou, Xingtao (Frontiers in Medicine, 2020)
Purpose: To investigate long-term changes in corneal densitometry (CD) following small incision lenticule extraction (SMILE) versus femtosecond laser-assisted LASIK (FS-LASIK) in patients with myopia or myopic astigmatism. Methods: Prospective analysis was performed in 66 eyes of 38 patients (13 males) who underwent SMILE and 54 eyes of 29 patients (5 males) who underwent FS-LASIK. In all patients, an ocular examination was performed preoperatively, and at 6-12 months and 5 years postoperatively. CD was obtained with Pentacam Scheimpflug imaging system at the 0-2-mm, 2-6-mm, and 6-10-mm zones of the cornea at depth of anterior 120 μm, midcornea, and posterior 60 μm. Correlation analysis was performed between postoperative change in CD and other variables such as age, type of surgery, central corneal thickness, spherical equivalent, lenticule thickness/ablation depth, and changes in wavefront aberrations. Results: At postoperative 6-12 months, a significant reduction at several corneal zones in the FS-LASIK cohort (P < 0.05) was observed. In the SMILE cohort, no significant change in CD relative to baseline was observed. However, at 5 years postoperatively, in both groups, a significant decrease in CD was observed in three zones of three layers (all P < 0.001). The change in CD was similar between groups at postoperative 6-12 months, but at 5 years the magnitude of change was significantly smaller in SMILE than FS-LASIK in the anterior and central layers (all P < 0.05). Conclusion: CD with Scheimpflug imaging system showed a significant decrease at 5 years after SMILE or FS-LASIK, and the change was significantly less pronounced after SMILE.